Structure–function coupling in the first month of life: Associations with age and attention - Ursula A. Tooley; Jeanette K. Kenley; M. Catalina Camacho; Aidan Latham; Dimitrios Alexopoulos; Ashley N. Nielsen; Tara A. Smyser; Barbara B. Warner; Joshua S. Shimony; Jeffrey J. Neil; Joan L. Luby; Deanna M. Barch; et al. (Proceedings of the National Academy of Sciences, 2025)
How brain structure relates to function is a critical and open question in neuroscience. Here, we characterize regional variation in structure–function coupling, capturing the degree to which a cortical region’s structural connections relate to patterns of coordinated neural activity in healthy, term-born neonates ( n = 239). Regional structure–function coupling is heterogeneously patterned across the cortex, with higher coupling in the auditory, lateral prefrontal, and inferior parietal cortices. Average structure–function coupling is negatively associated with age during the first month of life, with age-associated decreases seen in primary sensory systems, specifically in auditory and somatomotor regions. Age-associated “decoupling” of structure and function reflects increasingly segregated patterns of functional connectivity and increasingly integrated patterns of white matter connectivity with age. Notably, higher structure–function coupling after accounting for age in the dorsal attention, cingulo-opercular, and visual systems at birth is associated with faster visuospatial attention to faces at one year of age. These results yield valuable insight into the development of structural and functional connectivity across the cortex, including how interregional variation in structure–function coupling during the first month of life might shape later attention.